Effect of Modification of Mongolian Natural Zeolites on Adsorption of Chromium from Aqueous Solution - Bolortamir, Ts; Habaki, H; Egashira, R (Proceedings of the Mongolian Academy of Sciences, 2011)
Removal of chromium (Cr (III) ) as well as hexavalent chromium (Cr (VI) ) from tannery wastewater at same time by adsorption using Mongolian natural zeolite was studied in terms of the characteristics, modification, and chromium adsorption performance of the zeolite. The cation exchange capacity of the zeolite ranged from 37×10−3 to 144×10−3 eq·g−1. From the results of phase identification and elemental analysis of the zeolite after modification run, the zeolite was not decomposed and was modified successfully. The zeolites modified by Ba2+, Cu2+, and HDTMA-Br could adsorb Cr (III) as well as the unmodified one could. The higher pH gave the higher adsorption ability, similarly to the adsorption of Cr (VI). Consequently, this adsorption method with Mongolian natural zeolite was proposed to remove Cr (III) together with Cr (VI) from tannery wastewater at same time. DOI: http://dx.doi.org/10.5564/pmas.v0i4.49 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.71-77